1999
DOI: 10.1039/a901001g
|View full text |Cite
|
Sign up to set email alerts
|

XRD, TEM and 29Si MAS NMR study of sol-gel ZnO-SiO2 nanocomposites

Abstract: X-Ray amorphous ZnO nanoparticles homogeneously dispersed in a silica matrix were evidenced in ZnO-SiO2 nanocomposites obtained by a sol-gel method and heated to 700 degrees C. TEM observations indicated that the particle size slowly increases with temperature and zinc oxide content, reaching an upper limit of 12 nm. Through a comparison of the Si-29 MAS NMR data of the nanocomposites and silica samples, obtained by the same preparation method, it was possible to observe that reaction occurs between ZnO and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 13 publications
5
40
0
Order By: Relevance
“…It has been proved that the silica−zinc oxide complex can improve the dispersion of ZnO and control the nanoparticle size distribution by restraining the movement and aggregation of ZnO particles. 39,41 The above results further confirm that the structure of 3DOM had the similar effect. After the adsorption of hydrogen sulfide, clear and intense reflection peaks assigned to the ZnS phase appeared in the patterns of the sulfided samples (Figure 3c), indicating that the product of H 2 S sorption over the materials was ZnS.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…It has been proved that the silica−zinc oxide complex can improve the dispersion of ZnO and control the nanoparticle size distribution by restraining the movement and aggregation of ZnO particles. 39,41 The above results further confirm that the structure of 3DOM had the similar effect. After the adsorption of hydrogen sulfide, clear and intense reflection peaks assigned to the ZnS phase appeared in the patterns of the sulfided samples (Figure 3c), indicating that the product of H 2 S sorption over the materials was ZnS.…”
Section: Resultssupporting
confidence: 77%
“…However, the peaks of 3D-SZ20-500 and 3D-SZ50-500 at ∼25°shifted slightly toward angles larger than those corresponding to SiO 2 . 18,39 This shift might be due to introduction of ZnO and good dispersion of ZnO in the 3DOM composites. Moreover, a shoulder at ca.…”
Section: Resultsmentioning
confidence: 98%
“…Another strategy is to embed ZnO nanoparticles in inorganic host materials such as mesoporous silica [7][8][9][10][11][12][13], zeolite [14,15], ultrahard diamond-like carbon matrix [16], layered titanate [17,18], and montmorillonite [19]. The results show that the luminescent property was enhanced [10], and at the same time, the blue-shift of UV emission and blue emission, attributed to ZnOSiO 2 interface in the silica host [7,[10][11][12][13], were observed, or a new UV-Vis absorption edge, attributed to the formation of covalent bonds between the guest ZnO and host montmorillonite, emerged [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of the structure of blast furnace slag, a large amount of research has shown that the formation of an amorphous glass phase network is mainly the polymerization process of network formers [SiO 4 ] 4− and [Al 2 O 4 ] 5− through the connections among them by the bridged oxygen under quench conditions [19,[21][22][23][24]. The structural characteristics of the slag can be characterized by the bridged oxygen number, which can be obtained quantificationally and qualitatively by 29 Si and 27 Al MAS NMR [25,26]. As with nearly two decades of the rapid development of solid nuclear magnetic technology, especially for MAS NMR, which has been applied to the field of silicate building materials, researchers have conducted a large number of preliminary studies on the structure of vitreous in slag [27,28].…”
Section: Introductionmentioning
confidence: 99%